Komunikasi Politik Kepala Desa Dengan Badan Permusyawaratan Desa Dalam Mencegah Konflik Sosial - Maryani (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2022)
This research is motivated by the existence of vigilante actions carried out  by the residents of Sukaraja Village and the existence of misunderstandings. This study aims to discuss the political communication of the village chief and the Village Consultative Body in their role to prevent social conflict in Sukaraja Village, Semaka District, Tanggamus Regency and discuss influencing factors to prevent social conflict in Sukaraja Village, Semaka District, Tanggamus Regency using the Harold Lasswell paradigm. This study uses a descriptive method with a qualitative approach. The results showed that the village chief used interpersonal communication in his political communication with the Village Consultative Body to prevent social conflict. The interpersonal communication of the village head preventing social conflict uses an interactional communication model and a transactional communication model with the equalitarian style and the controlling style. Meanwhile, the interpersonal communication of the Village Consultative Body uses and interactional communication model with the equalitarian style of communication. The form of communication between the village head and the Village Consultative Body are in the form of conversation, dialogue and sharing.